Sh Waves in a Porous Layer of Nonuniform Thickness - Chattopadhyay, A.; Chakraborty, A. (Engineering Transactions, 1986)
The paper is concerned with the propagation of SH-waves due to momentary point sources, in a porous layer of nonuniform thickness resting on an isotropic elastic homogeneous half-space. Green's function techniques have been applied to salve the problem. The effects of porosity and nonuniformity on the displacement are distinctly marked. The possible condition creating fracture in the medium has also been derived. The graphs for the critical velocities of waves creating fracture in the medium versus thickness of the layer above the origin have been plotted at different modes.